Strategic approaches in promoting the corporate branding of Bank Muamalat Malaysia Berhad (BMMB) / Norazila Azimi - Azimi, Norazila (Faculty of Business Management, 2004)
Bank Muamalat Malaysia Berhad, the second full-fledged Islamic bank to be established in Malaysia after Bank Islam Malaysia Berhad, is poised to play its role in providing Islamic banking products and services to Malaysians, irrespective of race or religious beliefs, thus contributing to the development of modern Malaysia. It will clarify the extent to which Bank Muamalat current promotion are able to fulfill the consumers need. The research would be able to determine the promotional tools employed by Bank Muamalat whether the consumers aware about their brand name. Thus would enable existing strategies to be used in the future. It is because they have to create the best marketing mix strategies to provide the best for their consumers Based on the problem statement, this research was conducted to achieve these objective, (1) To determine the public awareness towards the Bank Brand (2) To identify whether the consumer's satisfied with the bank name and the bank logo, (3) To identify whether the consumer's satisfy the current promotional strategies towards Bank Muamalat Brand. This project paper consists of chapter. Chapter one is briefly discuss about the company background, problem statement and the objective of the study. Chapter two is Literature Review, where the topic and matters concerned is explain related to the study. Chapter three is Research Methodology, where the method of analyze of the study. Statistical Package for sosial Science (SPSS) has been used to analyze the data in term of frequency and cross tabulation. Chapter four is findings and interpretation and chapter five is conclusion and recommendation.